Le risque sédimentaire - Bedier, Edouard; Fleury, Pierre-gildas; Langlade, Aime; Haure, Joel; Le Roux, A.; Ropert, Michel; Rauflet, Fabienne; Soletchnik, Patrick (Présentation Séminaire MOREST, Caen, 14-26 novembre 2004, 2004)
The "sedimentary risk" has been identified since the mid-nineties in the Marennes Oléron Bay. The proximity of the sediment (from 0 to 15cms) increases the mortality rate. Depending on the year, mortality can be 10 to 20 % higher than in "high" conditions (50 to 70cms). These zootechnic results, gathered since 1996 on the working site of Ronces – Perquis, lead to the research of a pathogenic agent or a toxic substance released by the sediment. Studies conducted between 2002 and 2003 [12, 18] did not allow the identification of any pathogenic agents and ruled out the infectious risk. In 2004, the chemical risk (sulphides, ammoniacal nitrogen) was studied on 4 sites (3 working sites + Quiberon). In 2004, the "on-bottom/off bottom" mortality model of the Marennes Oléron Bay was transferred to Auray, Quiberon and Bay of Veys. The sedimentary risk has been confirmed for the Bay of Veys and for Quiberon (?) but not for Auray where the lack of significant differences between 15 and 70cms could only be the consequence of the homogeneity of the water column on a more hierologically unstable site! Le "risque sédimentaire" est identifié depuis le milieu des années 90 dans le Bassin de Marennes Oléron. La proximité du sédiment (0 à 15 cm) induit systématiquement plus de mortalité, et selon les années, de 10 à 20 % de plus qu'en condition "surélevé" (50-70 cm). Ces résultats zootechniques obtenus depuis 1996 sur les sites atelier de Ronces - Perquis conduisent à rechercher un agent pathogène ou une substance toxique libéré par le sédiment. Les études menées en 2002 et 2003 [12,18] ne permettent pas d'identifier d'agents pathogènes et éliminent également le risque infectieux. Le risque chimique (sulfures, azote ammoniacale) est étudié en 2004 sur 4 sites (3 sites atelier + Quiberon). En 2004, le modèle de mortalité plat-table du Bassin de Marennes Oléron est transposé sur Auray, Quiberon et Baie des Veys. Le risque sédimentaire est confirmé sur la Baie des Veys et sur Quiberon (?) mais pas sur Auray où la question se pose ...